Proposta de dicionário pedagógico bilíngue infantil espanhol-português - Miriam Cristiany Garcia Rosa (2018)
This research proposes the making of a bilingual pedagogical dictionary for children, SpanishPortuguese, illustrated, with a decoding function, designed for Spanish learners, as a foreign language (FL), from Elementary School (ES), ages 06 to 10. In order to reach our goal, based upon researches by Piaget, Vygotsky, Bruner, Brown, Jensen and Krashen, we have discussed the subsidiary theories of teaching a FL to those learners and how they learn a FL in the operational stage of the childhood development. We verified that these learners assimilate things more easily when presented with solid references and with more difficulty when reasoning about abstract references, in addition to learning faster in a fun, affective environment, based on their reality. We have also discussed about the making of a dictionary based on theoretical and practical assumptions of Lexicography and Pedagogical Lexicography from researches by Welker (2004, 2011), Carvalho & Bagno (2011), Garriga Escribano (2003), Castillo Carballo & García Platero (2003), Medina Guerra (2003) and Ferraz (2010, 2014). We have assumed that this type of dictionary’s terminology must be selected regarding the learners’ reality, therefore we compiled two corpora: the first one composed of 10 collections of Spanish didactic books from Elementary School, made in Brazil and Spain, in the last 20 years; the second one composed of 347 children’s short stories, made in Spain and available online. After a lexical analysis of both corpora, we have selected lexical words with frequency equal to or higher than 5 occurrences to be a part of the terminology. Some terminology units from other ES disciplines, as well as from new technologies, were included, resulting in a list composed of 2,603 simple and complex lexical units. The grammatical words, because of their own abstract character, will be placed in specific sections of the dictionary. Regarding the microstructural composition, we have based our research on Carvalho, Rossi and Lehmann’s studies and we have supported the use of phrasal definition that allows greater interaction with the child and more flexibility regarding metalanguage. We have proposed that both the entries and the definitions should be in Spanish, followed by their equivalent in Portuguese. We believe that these definitions may be as heterogeneous as the lexicon, therefore we have sought to use simple and concise definitions, but that refer to both the intralinguistic and the extralinguistic references, in order to provide concrete, sensorial and perceptive information, according to how the little seekers learn. Therefore, the definition model may be by assimilation and/or by script, as well as Aristotelian and/or ostensive etc. The examples are presented in both languages so that the child sees the use of lexical units in both languages, favoring the comprehension of the meaning. All the entries are illustrated in order to offer an iconic representation, associated with a symbolic representation of the language, fashioning 3 fundamental pillars – definition, example and illustration – harmonic, cohesive and coherent. At the end, we have presented a lexicographic proposition and a bilingual pedagogical dictionary, both new to the national market, in which the listed theories and the making of a dictionary, based of Pedagogical Lexicography, converge.